Burden of digestive system neoplasms in middle-aged and elderly adults: Temporal trends and geographic disparities (1990–2021) - Yinying Chai; Tinghui Xu; Bihua Chen; Yi Wu; Yibo He; Shengliang Qiu (PLoS ONE, 2025)
Objective This study aims to comprehensively analyze the temporal trends and geographic disparities in the burden of seven digestive system neoplasms—esophageal cancer, stomach cancer, colon and rectum cancer, liver cancer, gallbladder and biliary tract cancer, pancreatic cancer, and benign and in situ intestinal neoplasms—among middle-aged and elderly populations from 1990 to 2021, and to project future trends through 2035. Methods This study utilized data from the Global Burden of Disease (GBD) 2021 database to analyze the burden of seven digestive system neoplasms among middle-aged and elderly adults across 204 countries and territories from 1990 to 2021. Estimates of incidence, mortality, and disability-adjusted life years (DALYs) were extracted and stratified by year, sex, age group, region, and Socio-Demographic Index (SDI). Trends were evaluated using estimated annual percentage change (EAPC), and risk factors were analyzed using the GBD comparative risk assessment framework. Results In 2021, colon and rectum cancer dominated the global burden of digestive system neoplasms. Trends from 1990 to 2021 revealed a clear split: the incidence of colon and rectum cancer (EAPC = 0.26, 95% CI 0.19 to 0.33), liver cancer (EAPC = 0.25, 95% CI 0.82 to 1.38), pancreatic cancer (EAPC = 0.55, 95% CI 0.53 to 0.57), and benign intestinal neoplasms (EAPC = 1.1, 95% CI 0.82 to 1.38) rose globally, while esophageal (EAPC = −0.92, 95% CI −1.06 to −0.79), stomach (EAPC = −1.63, 95% CI −1.71 to −1.55), and gallbladder/biliary tract cancers (EAPC = −0.28, 95% CI −0.31 to −0.25) declined. Regional hotspots for burden were East Asia and High-income Asia Pacific. Males generally faced higher burdens, except for gallbladder and biliary tract cancer. Key risk factors included smoking, alcohol consumption, dietary patterns, and metabolic factors such as high BMI and elevated fasting plasma glucose. Conclusions The burden of digestive system neoplasms remains substantial in middle-aged and elderly adults, with significant regional differences. With the growing aging population, efforts should prioritize high-risk populations and invest in healthcare infrastructure in middle- and low-SDI regions to control established cancers. Additionally, implementing robust global prevention policies, such as expanding disease screening, raising public health awareness, and managing metabolic disorders, is essential to mitigate the rising tide of digestive system neoplasms.